Education on the Legal Aspects of Consumer Protection in Buying and Selling Transactions in the Electronic-based Millennial 5.0 Era (E-Commerce) - Rizal, Sofian Syaiful; Alnoor, Fatima Omer; Laily, Khofiyatul (IJECA (International Journal of Education and Curriculum Application), 2022)
Global economic integration has grown new economic powers and ASEAN countries. Technology and industry development requires competent human resources in every business organization. The presence of millennials and Generation Z has rapidly dominated the workforce, which, in the age of the Fifth Industrial Revolution, poses fresh difficulties to intercontinental rivalry. According to surveys, millennials are proficient with technology. However, due to the rise in cybercrime, its development has had a detrimental effect on the information technology sector. Data were gathered using qualitative research methods, a normative juridical approach, descriptive analysis, and internet literature reviews that created secondary data sources with three legal materials. The results of the study present legal protection education efforts for consumers that are carried out in a preventive, repressive, protective, solution and alternative way through dispute resolution, both litigation and non-litigation channels, so it is necessary to build a legal remedy. umbrella that can anticipate the rapid development of information and communication technology, especially in the e-commerce sector. trade and legal aspects of consumer protection.